Intestinal perforation after regorafenib usage - Barış Sarıcı; Serdar Karakaş; Ufuk Uylas; Aydın Aktaş; Mustafa Dikilitaş; Cüneyt Kayaalp (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Sarıcı B, Karakaş S, Uylas U, Aktaş A, Dikilitaş M, Kayaalp C. Intestinal perforation after regorafenib usage. Turk J Gastroenterol 2018; 29: 245-7.